Analisis Strategi Pemasaran Serta Tingkat Kepuasan Konsumen Kentucky Fried Chicken (KFC) - Yudha, Eka Purna; Mirfazli, Miluniqa Yasmin; Farhan, Fahmi Muhammad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This study aims to determine the marketing strategy and the level of consumer satisfaction with the products of the transnational company kentucky fried chicken (KFC). Data collection is done online, questionnaires are distributed to consumers who have visited KFC in West Java. The analysis method used is Important Performance Analysis (IPA) and Costumer Satisfaction Index (CSI). The results of this study indicate that Kentucky Fried Chicken (KFC) has carried out the 7P marketing strategy (Product, Place, Price, Promotion, People, Process, Physical Evidence) in West Java well, as evidenced by the calculation of CSI and IPA that has been done. From the CSI value of 81.36 located in the range of 80% - 100% which indicates that the level of consumer satisfaction with KFC is classified as "Very Satisfied". Based on IPA, KFC needs to do product differentiation, which makes the food products it sells have their own characteristics.